2020
DOI: 10.37393/jass.2020.02.4
|View full text |Cite
|
Sign up to set email alerts
|

Agreeement Between Measurement of Jump Height in Different Vertical Jump Tests Executed by Young Football Players

Abstract: Football is an intermittent sport with a great number of short and explosive actions. These characteristics of the game require a good level of anaerobic power. The main field tests used as indicators of the development of the anaerobic energy system were the jumps in the vertical plane. The same tests also measured the strength of the lower limbs. We presume that the explosive power of the lower limbs characterizes the development of the alactic anaerobic energy system and strength capacity at the same time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Our findings are in accordance with many studies found in the literature investigating the validity of inertial measurements systems for determining two-leg CMJ heights [ 11 , 12 , 13 , 14 , 27 ]. McHugh et al [ 27 ] observed that two-leg CMJ flight heights were strongly correlated between the optoelectronic system and an inertial sensor, but the latter underestimates the flight height values (1.8 ± 1.8 cm).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are in accordance with many studies found in the literature investigating the validity of inertial measurements systems for determining two-leg CMJ heights [ 11 , 12 , 13 , 14 , 27 ]. McHugh et al [ 27 ] observed that two-leg CMJ flight heights were strongly correlated between the optoelectronic system and an inertial sensor, but the latter underestimates the flight height values (1.8 ± 1.8 cm).…”
Section: Discussionsupporting
confidence: 93%
“…Vertical jump quantitative motion measurements with inertial sensors have been validated already [ 3 , 11 , 12 , 13 , 14 ] and a further study investigated the concurrent validity of inertial sensors compared to force plates for an assessment of the flight times of counter movement jumps (CMJs) in professional male soccer players (18 ± 3 years), showing excellent intraclass correlation coefficient (ICC) values (0.92–0.97) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vertical jump performance has been well-studied in the past (Mackala, et al, 2013;Gadev et al, 2020). An important aspect of vertical jump performance is the contribution of upper limb segments to force production during jump takeoff (Fukashiro, et al, 2005;Linthorne, 2001).…”
Section: Introductionmentioning
confidence: 99%